Demystifying TRIZ for achieving ideality in design of technical systems - Raneses, Nestor O.
This paper describes the basic foundations of TRIZ in simple operational terms and affirms its empirical soundness in generating innovative solutions to inventive problems. Three actual case study applications are presented to demonstrate how the basic methods and tools of TRIZ can be used to structure and accelerate inventive solution finding. We conclude that assimilating TRIZ in design oriented courses is a good anchor for introducing and diffusing TRIZ technology and innovative thinking in graduate design course and in capstone design courses in the undergraduate levels.
Keywords: Inventive problem; Ideality; Functionality; Resources; Contradictions; Inventive principles; Su-F models; Technology evolution; ARIZ